2017
DOI: 10.1089/pho.2016.4150
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Laser Therapy and Cryotherapy as Mono- and Adjunctive Therapies for Achilles Tendinopathy in Rats

Abstract: Our results demonstrate that cryotherapy in combination with LLLT can produce an anti-inflammatory "add-on" effect. The order of therapy administration seems essential, as superior histology and biomechanical results were found in the cryotherapy first/LLLT group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 232 publications
(304 reference statements)
0
19
0
7
Order By: Relevance
“… 14 In animal injury models, gene, and protein expression of IL-6 was increased from two hours to four weeks after the intervention. 18 , 19 , 21 , 26 , 46 The effect of exercise was inconsistent in animal models. 26 , 27 , 36 , 38 , 40 IL-6 treatment on tendon cells did not have any effect on the expression of tendon ECM genes and proteins.…”
Section: Resultsmentioning
confidence: 99%
“… 14 In animal injury models, gene, and protein expression of IL-6 was increased from two hours to four weeks after the intervention. 18 , 19 , 21 , 26 , 46 The effect of exercise was inconsistent in animal models. 26 , 27 , 36 , 38 , 40 IL-6 treatment on tendon cells did not have any effect on the expression of tendon ECM genes and proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of infrared radiation on nerves has been shown in the literature in relation to the photobiological mechanisms of infrared LED, which has an anti‐inflammatory action, such as the modulation of cyclooxygenases and lipoxygenases and the reduction of inflammatory mediators such as prostaglandins, prostacyclins, bradykinin, histamine, substance P, interleukin 1 beta, and tumor necrosis factor alpha, decreasing the activation of the nociceptors . In addition, many studies have shown satisfactory results in relation to the effects of infrared, near‐infrared, or both wavelengths on different pathological conditions such as burn wounds, postsurgery pain, Achilles tendinopathy, hip arthroplasty, knee osteoarthritis, and oral mucositis, where there is an inflammatory process. It is very important to understand whether the chromophores activated by different wavelengths are correlated with the individual responses or eventual cumulative response of both wavelengths in the same treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Fotobiomodulação (FBM) é uma descrição das intervenções com terapia de luz que modula processos biológicos (HASLERUD et al, 2017). A Terapia com Laser de Baixa Intensidade (TLBI), nos comprimentos de onda do vermelho e do infravermelho, constitui o subtipo da FBM mais empregado em estudos ao longo dos anos, demonstrando resultados favoráveis na modulação do processo inflamatório, controlando edema, hemorragia, necrose tecidual e influxo de neutrófilos, bem como controlando a atividade das células inflamatórias.…”
Section: Considerandounclassified